Blocking statutes and cross-border taking of evidence - Muyo Bussac, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper makes a balanced study of whether it is legitimate (and if so, within what limits) for the parties to a dispute or the court hearing the case to be able to use unilaterally and with extraterritorial effect instruments for obtaining evidence other than those provided for in the instruments of legal cooperation on the gathering of evidence, when the information or its support is or has to be produced abroad. In doing so, it critically assesses and contrasts the reasons that legitimise the unilateral and extraterritorial gathering of information sources abroad with the blocking statutes, which are designed to prevent such a course of action.